Exposure of Ticks Rhipicephalus sanguineus sensu lato (Acari:Ixodidae) to Ozonated Water: Integument Response - Abreu, Marina Rodrigues de [UNESP]; Delalibera Junior, Italo; Pereira, Natalia Rubio Claret [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Taylor & Francis Inc, 2020)
The Rhipicephalus sanguineus s. l. has great medical and veterinary importance posing severe risks to the well-being of pets and public health. The ozone is a promising alternative for control of this ectoparasites, by not causing environmental contamination or threatening public health. Due to the fact that the integument is the organ that first comes into contact with topically applied acaricides, the objective of this study was to investigate morphological alterations in ticks exposed in vivo to ozonated water for 5 min and analyzed after the periods of 24, 48, and 72 h. The results showed that the exposure to ozonated water at the concentration of 2.25 mg/L for 5 min and analyzed after 48 h had the greatest effect, causing irreversible damage to the integument of the R. sanguineus s. l. females, interfering in the processes of attachment, engorgement, and reproduction.
Keywords: Ozone; tick; control; integument; acaricide; morphology